ANALISIS FAKTOR PENGHAMBAT KEBIJAKAN REFORMASI ADMINISTRASI DI SEKRETARIAT JENDERAL KEMENTERIAN ENERGI DAN SUMBER DAYA MINERAL - Ramadhani Haryo Seno; Eko Prasojo (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2019)
The focus of this research is to describe the implementation of administrative reform, explain its impeding factors, and propose recommendations in dealing with the obstacles faced by The Secretariat General of Ministry of Energy and Mineral Resources. Post-positivism with qualitative design method is used for this research. The results show that the contents of the policy become an inhibiting factor, while its contexts do not. There are two proposed recommendations including intensively and massively implementing the joint forum for socialization, internalization, and education to discuss four indicators such as affecting interests, type of benefits, extent of change envision, and program implementors related to administrative reform to a more substantial level instead of formality. In addition, it is highly recommended creating urgency of administrative reform as the main agenda and priority of all organization entities